2010
DOI: 10.4061/2010/741751
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Lead Perforation: Can We Ever Let the Guard Down?

Abstract: Lead perforation is a major complication of cardiac rhythm management devices (CRMD), occurring in about 1%. While most lead perforations occur early, numerous instances of delayed lead perforation (occurring >30 days after implantation) have been reported in the last few years. Only about 40 such cases have been published, with the majority occurring <1 year after implantation. Herein, we describe the case of an 84-year-old female who presented with recurrent syncope and was diagnosed to have delayed pacemake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…[2][3][4][5] Perforations are typically seen within hours or the first days after implantation; however, recent literature suggests a trend towards delayed lead perforations. 6,7 The case presented is remarkable as it describes, on the one hand, a very late lead perforation after implantation and, on the other hand, the gradual perforation process which is assumed to be typical for late lead perforations. 4 In retrospect, the different symptoms reported by the patient can be explained by a stepwise perforation process.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Perforations are typically seen within hours or the first days after implantation; however, recent literature suggests a trend towards delayed lead perforations. 6,7 The case presented is remarkable as it describes, on the one hand, a very late lead perforation after implantation and, on the other hand, the gradual perforation process which is assumed to be typical for late lead perforations. 4 In retrospect, the different symptoms reported by the patient can be explained by a stepwise perforation process.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of literature done by Refaat et al, the mean time of late lead perforation was found to be 4.64 months [1]. In a review of 38 cases of late lead perforation done by Alla et al, majority of the cases occurred between 6 weeks to 1 year after implantation with 8 out of 38 cases occurring after 1 year [35], one of which presented after 3 years. Alla et al had also reported one case with lead perforation occurring close to 5 years after implantation [35].…”
Section: Discussionmentioning
confidence: 94%
“…The majority of perforations manifest within a year but rarely cases have been reported as late as five years following implantation. [6] 1.2. RV perforation…”
Section: Incidence and Time Course For Cardiac Perforationmentioning
confidence: 99%